Emergence of SARS-CoV-2 Alpha (B.1.1.7) variant, infection rates, antibody seroconversion and seroprevalence rates in secondary school students and staff: Active prospective surveillance, December 2020 to March 2021, England. Issue 5 (November 2021) - Ladhani, Shamez N.; Ireland, Georgina; Baawuah, Frances; Beckmann, Joanne; Okike, Ifeanyichukwu O; Ahmad, Shazaad; Garstang, Joanna; Brent, Andrew J; Brent, Bernadette; Aiano, Felicity; Amin-Chowdhury, Zahin; Kall, Meaghan; et al.
Highlights: By march 2021, SARS-CoV-2 nucleoprotein antibody positivity was 36.3%. During lockdown, 14% of students and 10% of staff had N-antibody seroconverted. Weekly seroconversion rates were similar during lockdown to autumn term rates. Summary: Objectives: We assessed SARS-CoV-2 infection, seroprevalence and seroconversion in students and staff when secondary schools reopened in March 2021. Methods: We initiated SARS-CoV-2 surveillance in 18 secondary schools across six regions in September 2020. Participants provided nasal swabs for RT-PCR and blood samples for SARS-CoV-2 antibodies at the beginning (September 2020) and end (December 2020) of the autumn term and at the start of the spring term (March 2021). Findings: In March 2021, 1895 participants (1100 students:795 staff) were tested; 5.6% (61/1094) students and 4.4% (35/792) staff had laboratory-confirmed SARS-CoV-2 infection from December 2020-March 2021. Nucleoprotein-antibody seroprevalence was 36.3% (370/1018) in students and 31.9% (245/769) in staff, while spike-antibody prevalence was 39.5% (402/1018) and 59.8% (459/769), respectively, similar to regional community seroprevalence. Between December 2020 and March 2021, 14.8% (97/656; 95%CI: 12.2–17.7) students and 10.0% (59/590; 95%CI: 7.7–12.7) staff seroconverted. Weekly seroconversion rates were similar from September to December 2020 (8.0/1000) and from December 2020 to March 2021 (7.9/1000; students: 9.3/1, 000; staff: 6.3/1, 000). Interpretation: By March 2021, a third of secondary school students and staff had evidence of prior infection based on N-antibody seropositivity, and an additional third of staff had evidence of vaccine-induced immunity based on S-antibody seropositivity.